Modulation of Septo-Hippocampal Neural Responses in Anesthetized and Behaving Rats by Septal AMPA Receptor Mechanisms - Ibrahim, Khairunisa Mohamad; Ariffin, Mohammed Zacky; Khanna, Sanjay (Frontiers in Neural Circuits, 2021)
This study explored the effects of septal glutamatergic transmission on septal-hippocampal theta activity via intraseptal microinjection of antagonist at AMPA receptors (AMPAR). The current results showed that microinjection of AMPAR antagonist, NBQX (2,3-dihydroxy-6-nitro-7-sulfamoyl-benzo[f]quinoxaline-2,3-dione, 20 μg/μl, 0.5 μl), evoked a decrease in the frequency of theta activity evoked by various means in anesthetized and behaving rat. Theta wave activity was induced on: (a) intraseptal microinjection of carbachol, an agonist at cholinergic receptors, (b) reticular stimulation, (c) exploration in novel open field (OF), and (d) hind paw (HP) injection of the algogen, formalin. The effect on frequency in the formalin test was observed in an early period on injection of formalin, which was novel to the animal, but not in the later more sustained phase of the formalin test. The effect of NBQX, being seen in both anesthetized and behaving animals, suggests that the modulation of theta wave frequency, including in novelty, is a function of AMPAR in MS. The effect of the antagonist on theta power was less apparent, being observed only in anesthetized animals. In addition to theta power and frequency, intraseptal NBQX also attenuated suppression of CA1 population spike (PS) induced by intraseptal carbachol, thus suggesting that septal glutamate neurotransmission is involved in the spectrum of MS-mediated network responses. Indeed, in the context of behavior, formalin injection induced an increase in the level of septal glutamate, while NBQX attenuated nociceptive behaviors. Notably, MS is involved in the modulation of formalin nociception. These findings suggest that AMPA receptors are a key modulator of septal physiological function.